2001
DOI: 10.1021/ie010024u
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Fractional Crystallization Method for the Enrichment of γ-Linolenic Acid in Borage Oil Fatty Acid

Abstract: A two-stage, low-temperature solvent fractional crystallization process was developed in this work for the enrichment of γ-linolenic acid (GLA, 18:3 n6) in free fatty acids (FFAs) derived from saponified borage oil. Acetonitrile was the solvent in the first stage. At an acetonitrile to FFA ratio of 62.5 mL/g and after 48 h of storage at -40 °C, the GLA content in the liquid phase can be increased from 23.4% to 66.1% with a corresponding yield of 93.0%. In the second stage, a mixture of 30% acetonitrile and 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The reaction was performed in 50 mM citrate/phosphate buffer (pH 6.0) containing 100 g linoleic acid l -1 , 25 g cells l -1 , and 0.25 % (v/v) tween 40 at 40°C for 5 h . The fraction of hydroxy fatty acid in the reaction solution was collected by solvent fractional crystallization at low-temperature (Chen and Ju 2001). An equal volume of ethyl acetate was added to the product solution, and the solvent was removed from the solution using a rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was performed in 50 mM citrate/phosphate buffer (pH 6.0) containing 100 g linoleic acid l -1 , 25 g cells l -1 , and 0.25 % (v/v) tween 40 at 40°C for 5 h . The fraction of hydroxy fatty acid in the reaction solution was collected by solvent fractional crystallization at low-temperature (Chen and Ju 2001). An equal volume of ethyl acetate was added to the product solution, and the solvent was removed from the solution using a rotary evaporator.…”
Section: Methodsmentioning
confidence: 99%
“…Use of hexane makes this procedure suitable when working with alimentary purposes, being also useful because it is easy to use at industrial scale [18]. Fractional crystallization method has been used to obtain an enriched GLA fraction from borage oil, by a two-stage process [57]. In the first stage (low-temperature crystallization), the solvent employed was acetonitrile (ACN), while in the second stage the solvent used was a mixture of ACN/ acetone (30:70 v/v).…”
Section: Low-temperature Crystallizationmentioning
confidence: 99%
“…It has been reported that use of different organic solvents and temperatures affect the concentration of PUFA and thus, proper choice of solvent and temperature is necessary to achieve optimal concentration yield of the x-3 PUFA [5,17]. Chen and Ju [18] concentrated GLA by means of a twostep solvent crystallization process of Borago officinalis free fatty acids. Nevertheless, this procedure was attempted using acetonitrile as solvent, which should be avoided in any bioprocess to obtain dietary products, because it is widely reported to be harmful to humans.…”
Section: Introductionmentioning
confidence: 99%